2018
DOI: 10.1001/jamaophthalmol.2018.3556
|View full text |Cite
|
Sign up to set email alerts
|

Association of Preclinical Alzheimer Disease With Optical Coherence Tomographic Angiography Findings

Abstract: IMPORTANCE Biomarker testing for asymptomatic, preclinical Alzheimer disease (AD) is invasive and expensive. Optical coherence tomographic angiography (OCTA) is a noninvasive technique that allows analysis of retinal and microvascular anatomy, which is altered in early-stage AD.OBJECTIVE To determine whether OCTA can detect early retinal alterations in cognitively normal study participants with preclinical AD diagnosed by criterion standard biomarker testing. DESIGN, SETTING, AND PARTICIPANTSThis case-control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
209
4
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(235 citation statements)
references
References 52 publications
(81 reference statements)
9
209
4
6
Order By: Relevance
“…The discovery of pathogenic Aβ deposits and early pericyte loss in retinal blood vessels of MCI and AD could shed light onto the pathophysiological mechanisms of vascular disruption, increased BRB permeability, insufficient blood supply, disrupted immune responses, and neuronal degeneration. In light of the recent advances in live imaging of retinal blood microvessels (OCT angiography) [26,42,62,82], pericyte imaging using adaptive optics [68], and retinal amyloid imaging [35,47], these results should lead to future development of noninvasive retinal vascular amyloid and pericyte imaging technologies to facilitate early screening and monitoring of AD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The discovery of pathogenic Aβ deposits and early pericyte loss in retinal blood vessels of MCI and AD could shed light onto the pathophysiological mechanisms of vascular disruption, increased BRB permeability, insufficient blood supply, disrupted immune responses, and neuronal degeneration. In light of the recent advances in live imaging of retinal blood microvessels (OCT angiography) [26,42,62,82], pericyte imaging using adaptive optics [68], and retinal amyloid imaging [35,47], these results should lead to future development of noninvasive retinal vascular amyloid and pericyte imaging technologies to facilitate early screening and monitoring of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the pathological hallmarks of AD-Aβ plaques and tauopathy-were further identified in the retina of AD patients, including early-stage cases [25,46,47,50]. Noninvasive high-resolution retinal imaging technologies such as fundus imaging, optical coherence tomography (OCT), as well as recently developed OCT angiography [42,62,72], retinal amyloid imaging [46][47][48], and retinal hyperspectral imaging [35,59] incentivize the use of feasible and inexpensive retinal imaging in the clinical setting to improve AD screening and monitoring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of 14 participants with biomarkers (PET Scan and/or Aβ 42 protein) positive for AD (preclinical AD), but cognitively healthy based on neuropsychometric testing, O'Bryhim et al concluded that the FAZ was larger and the inner fovea was thinner compared to controls. 13,14…”
Section: Is Oct Angiography Useful In Neurodegenerative Diseases?mentioning
confidence: 99%
“…Golzan et al observed a slight GCL thinning in 28 AD dementia patients compared to 50 Aβ− controls but no differences with preclinical AD individuals [44]. O'Bryhim et al detected an increase in the foveal avascular zone area and a reduction in the inner foveal thickness in an Aβ+ group (n = 14) compared to 16 controls [45]. Recently, van de Kreeke et al did not detect differences in macular or RNFL thickness between 18 Aβ+ and 147 Aβ− healthy elderly monozygotic twins [46].…”
Section: Discussionmentioning
confidence: 99%